The Impact of Patriarchial Cultural Reconstruction on Women's in Central Lombok - Pahmi, Zul; Suparman, Suparman; Sarwadi, Gita; Kholid, Kholid (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Pessimism is defined as a psychological condition characterized by feelings of low self-esteem, helplessness, and submission to male dominance. This article explores how the reconstruction of patriarchal culture affects the development of pessimistic attitudes among women in Central Lombok society. This research uses a descriptive qualitative approach, involving in-depth interviews with 15 women from three villages (Sengkerang, Ganti, and Pengonak) selected through purposive sampling, participatory observation, and relevant literature review. Data analysis was conducted qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The findings indicate that patriarchal norms are deeply entrenched through strict division of domestic roles and the marginalization of women's rights in education and public decision-making. This situation leads to pessimism, evidenced by limited social involvement, low economic initiative, and reluctance to voice opinions. Nevertheless, resistance persists among young women who are involved in local organizations, pursue higher education, and develop micro-enterprises in the creative economy. This study underscores that, despite the continued dominance of patriarchal structures, social dynamics are gradually creating opportunities for women's empowerment in Central Lombok.